The role of rational and emotional appeals on website promotion - Lwin, Michael (School of Marketing, Curtin Business School, 2009)
The purpose of this paper is to examine the effectiveness of rational and emotional appeals in an online context. A review of the literature revealed intangible appeals maybe more appropriate for services due to service intangibility. Using websites as cues, it compares the differences between the two appeals in the context of boutique hotels. Results indicate emotional appeals are more effective than rational appeals. Findings imply that boutique hotels should use emotional appeals online to create a point of difference, and to maximise the return from investment due to their small advertising budget. This research extends the use of emotional appeals on a new medium.